Analisis Faktor-Faktor Yang Mempengaruhi Trust Dan Pengaruhnya Terhadap Willingness To Pay A Premıum Prıce Pada Layanan Premium Online Streaming - Erilia Kesumahati; Yogi Marbun (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
This study aimed to analyze the factors that influence trust and their influence on willingness to pay a premium price on premium online streaming services. The independent variables used in this study were service quality, service convenience, sophistication, product quality, and brand image. While the dependent variables used were trust and willingness to pay a premium price. The sample used for this study was 226 community respondents in Batam City using the purposive sampling method, i.e using the criteria of people who used premium online streaming services as research respondents. Data analysis was performed using SPSS version 26.0 software for demographic analysis of respondent data and Common Method Bias (CMB) test, as well as SmartPLS software version 3.0 for hypothesis testing. The results of this study indicated that service quality, product quality, and brand image have significant positive effect on trust. Service convenience and sophistication have no significant positive effect on trust. Meanwhile, trust has a significant positive effect on willingness to pay a premium price. Based on the results of this study, it is seen the importance of providing service quality, product quality, and building a good brand image in creating trust from a premium online streaming service in order to raise willingness to pay a premium price in the community in the midst of intense market competition.